First Observations of a Deep‐Water Seagrass Meadow (Thalassodendron ciliatum) on an Oceanic Reef in the Southern Coral Sea Marine Park, Australia - G. F. Galbraith; B. J. Cresswell; M. Russell; A. S. Hoey (Ecology and Evolution)
ABSTRACT Tropical seagrass meadows are important global marine ecosystems that provide critical ecosystem goods and services. The extent of global seagrass meadows is mostly mapped from shallow coastal regions and not well known or sampled from deeper offshore locations. Seagrasses can, however, form deep‐water meadows, which likely significantly increase the total area of global seagrass ecosystems and may contribute important ecological functions to offshore tropical seascapes. Here we report the first observation of a dense meadow of Thalassodendron ciliatum at a depth of 25 m using remotely operated vehicles (ROVs) from the Coral Sea Marine Park (CSMP). Despite significant survey effort in the region, to date there have only been three other observations of seagrass in the CSMP, all sparse and small patches of Halophila ovalis and Halophila decipiens. We discuss the significance of this newly discovered meadow within the context of current reef health monitoring of the CSMP, reef fish biodiversity and the ecological value of deep‐water seagrass habitats for offshore coral reef systems like the Coral Sea.